ANALISIS HUBUNGAN ANTARA KEPEMIMPINAN, IKLIM ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH UPT SAMSAT MEDAN SELATAN - Imelda Fitri; Ismed .; Kemal Idris Batubara; Purnama Waruwu; Yose Rizal Siregar (Universitas Islam Sumatera Utara, 2021)
This research discusses about the relationship between leadership, organizational climate, and work environment towards employees’ work satisfaction at Regional Tax and Retribution Management, UPT Samsat Medan Selatan. The aim of this research is to analyse the relationship between leadership, organizational climate, and work environment both partially and simultaneously on employees’ work satisfaction at the office. This is a quantitative research with random sampling technique. The sample is 63 employees. Results show that each independent variable; leadership, organizational climate, and work environment, partially influences employees’ work satisfaction positively and significantly. leadership has tcount value 4,810 and level of significance 0.000, organizational climate has 2,241 and 0.029, and work environment has 2,518 and 0.015. Simultaneously, leadership, organizational climate, and work environment have significant and positive relationship on employees’ work satisfaction at Regional Tax and Retribution Management, UPT Samsat Medan Selatan with Fcount value 19,943 and level of significance 0.000.